The Problem of First-Year Seminars: Risking Disengagement Through Marketplace Ideals - Hickinbottom-Brawn, Sarah; Burns, David P. (Canadian Journal of Higher Education, 2015)
First-year seminars (FYS) have become increasingly prevalent in North American postsecondary institutions. The popularity of such initiatives owes much to the belief that providing unprepared students general life and academic skills can bolster engagement and thereby improve retention. In this paper we argue that, despite their good intentions, many FYS actually perpetuate the kind of disengagement they were designed to alleviate due to their reliance on a narrow, instrumental view of education. To demonstrate, we briefly outline the history and curricula of the FYS movement to draw attention to its dependence on marketplace ideals, rationales, and strategies. We demonstrate some of the ways this vision of education impoverishes the university experience and suggest that, in order to be robust, FYS must focus first and foremost on cultivating rich understandings of the broader purposes of higher education and its relation to the good life, both for and beyond one’s own fulfillment.